Hubungan Intensitas Penggunaan Media Sosial TikTok dengan Prokrastinasi Akademik Pada Mahasiswa - Ricka Yoseva; Ratna Yunita Setiyani Subardjo (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The intensity of TikTok social media use is the frequency or amount of time spent using TikTok social media. Academic procrastination is the deliberate delay in completing tasks related to academic activities. This study aims to determine whether there is a relationship between the intensity of TikTok social media usage and academic procrastination among university students. This research employs a descriptive quantitative method. A total of 382 active university students in Indonesia participated in the study. Data were collected through an online survey using Google Forms, measuring the relationship between the intensity of TikTok social media usage and academic procrastination, and were then analyzed using assumption tests, linear tests, and hypothesis testing. The results indicate a significant relationship with academic procrastination among students (r = 0.744, p < 0.05), meaning that the higher the intensity of TikTok social media usage, the higher the level of academic procrastination among students. Although this study was conducted successfully, there are several limitations, such as the need for respondents with more diverse backgrounds and consideration of other influencing factors.